Process evaluation of the Cancer Home-Life Intervention: What can we learn from it for future intervention studies?. (December 2020) - la Cour, Karen; Gregersen Oestergaard, Lisa; Brandt, Åse; Offersen, Sara Marie Hebsgaard; Lindahl-Jacobsen, Line; Cutchin, Malcolm; Pilegaard, Marc Sampedro
Background: The Cancer Home-Life Intervention showed no significant effects, and examination of the processes affecting or inhibiting outcomes is relevant. Aim: To evaluate the Cancer Home-Life Intervention for its processes of implementation, mechanisms of impact and contextual factors. Design: Process evaluation conducted alongside the randomised controlled trial, using quantitative and qualitative methods (ClinicalTrials.gov NCT02356627). The Cancer Home-Life Intervention is a tailored, occupational therapy–based programme. Setting/participants: This study took place in participants' homes and at hospital. A total of 113 home-dwelling adults (⩾18 years) with advanced cancer who had received the Cancer Home-Life Intervention were included, together with five intervention-therapists. Results: All 113 participants (100%) received a first home visit; 32 participants (26%) received a second visit; and 4 participants (3%) received a third visit. Median number of delivered intervention components were 3 (interquartile range: 2; 4). Identified barriers for effect included unclear decision process for intervention dosage; participants' low expectations; participants' lack of energy; and insufficient time to adopt new strategies. The trial design constituted a barrier as the intervention could only be provided within a specific short period of time and not when relevant. Intervention components working to solve practical everyday problems, enhance enjoyment and increase a sense of safety were perceived as useful. Conclusion: Future interventions can benefit from inclusion criteria closely related to the intervention focus and clear procedures for when to continue, follow-up and terminate intervention. Decisions about dose and timing may benefit from learning theory by taking into account the time and practice needed to acquire new skills.